Spatial partitioning of the regulatory landscape of the X-inactivation center - Nora, Elphège P. (2012)
The mouse X-inactivation center (Xic) orchestrates initiation of X inactivation by controlling the expression of the non-coding Xist transcript. The full extent of Xist’s regulatory landscape remains to be defined however. Here we use Chromosome Conformation Capture Carbon-Copy and super-resolution microscopy to analyse the spatial organisation of a 4.5Mb region including Xist. We uncover a series of discrete 200kb-1Mb topologically associating domains (TADs), present both before and after cell differentiation and on the active and inactive X. These domains align with several domain-wide epigenomic features as well as co-regulated gene clusters. Disruption of a TAD boundary causes ectopic chromosomal contacts and long-range transcriptional mis-regulation. Xist/Tsix illustrates the spatial segregation of oppositely regulated chromosomal neighborhoods, with their promoters lying in two adjacent TADs, each containing their known positive regulators. This led to the identification of a distal regulatory region of Tsix producing a novel long intervening RNA, Linx, within its TAD. In addition to uncovering a new principle of the cis-regulatory architecture of mammalian chromosomes, our study sets the stage for the full genetic dissection of the Xic.